1987
DOI: 10.1002/jnr.490180407
|View full text |Cite
|
Sign up to set email alerts
|

Capacity for substrate utilization in oxidative metabolism by neurons, astrocytes, and oligodendrocytes from developing brain in primary culture

Abstract: Neuron, astrocyte, and oligodendrocyte cultures which were established from developing rat brain were examined for their utilization of glucose, ketone bodies, and free fatty acids by oxidative processes. 14CO2 production was measured in these cells from [1-14C] or [6-14C]glucose; [1-14C]octanoate and [1-14C], [6-14C], or [16-14C]palmitate; and [3-14C]acetoacetate and D(-)-3-hydroxy[3-14C]butyrate. Pyruvate dehydrogenase (EC 1.2.4.1.) and 3-oxoacid-CoA transferase (EC 2.8.3.5) activities were found at high lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
252
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(284 citation statements)
references
References 59 publications
22
252
0
3
Order By: Relevance
“…As the interest in alternative metabolic substrates for metabolic therapy grows, it becomes increasingly important to document both cerebral uptake and metabolism of these substrates under various cerebral pathological states. Previous studies utilizing in vivo models have only demonstrated substrate uptake (Hawkins et al 1971;Chen et al 2000); studies demonstrating both substrate uptake and oxidation have been limited to in vitro experiments (Brandt et al 1984;Yu et al 1984;LopesCardozo et al 1986;McKenna et al 1986McKenna et al , 1994Edmond et al 1987;Westergaard et al 1994;Waniewski and Martin 1998). The present study applied a modified in vivo approach to measure both cerebral uptake and metabolism of the alternative substrate bHB and demonstrate the value of such an approach in studying cerebral injury.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…As the interest in alternative metabolic substrates for metabolic therapy grows, it becomes increasingly important to document both cerebral uptake and metabolism of these substrates under various cerebral pathological states. Previous studies utilizing in vivo models have only demonstrated substrate uptake (Hawkins et al 1971;Chen et al 2000); studies demonstrating both substrate uptake and oxidation have been limited to in vitro experiments (Brandt et al 1984;Yu et al 1984;LopesCardozo et al 1986;McKenna et al 1986McKenna et al , 1994Edmond et al 1987;Westergaard et al 1994;Waniewski and Martin 1998). The present study applied a modified in vivo approach to measure both cerebral uptake and metabolism of the alternative substrate bHB and demonstrate the value of such an approach in studying cerebral injury.…”
Section: Discussionmentioning
confidence: 65%
“…Although glucose remains the primary cerebral metabolic substrate under normal conditions, there are many physiological states during which the brain's reliance on glucose shifts to alternative substrates (Owen et al 1967;Hawkins et al 1971;Dahlquist and Persson 1976;Kries and Ross 1992;Vannucci and Vannucci 2000). In vitro studies have documented uptake and oxidation of 14 C-labeled glycerol (McKenna et al 1986a) (Edmond et al 1987). However, ketone bodies such as bHB are the only endogenously circulating alternative substrates that have been shown significantly to supplement cerebral metabolism (Owen et al 1967;Hawkins et al 1971;Dahlquist and Persson 1976).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2B). Although previous studies indicated that minimal fatty acid oxidation occurs in neurons as compared with other tissues (46), experiments were performed to determine whether C75 could alter the rate of fatty acid oxidation in cortical neurons, as it did in peripheral tissues (10). The level of total fatty acid oxidation was determined by combining the 14 C-labeled acid soluble and CO 2 products obtained after the addition of [1-14 C]palmitate.…”
Section: C75 Inhibits Fas and Stimulates Cpt-1 And Fatty Acid Oxidatimentioning
confidence: 99%
“…However, at that time, this ratio (approximately 1) was very favorable (Simopoulos, 2006). Non-converted ALA undergoes aerobic b-oxidation in the astrocyte mitochondrion (Edmond et al, 1987) and is fully degraded into acetyl-CoA (Lynen's helix). The latter occurs in several synthesis pathways, including the production of ATP (Krebs cycle and the respiratory chain), lipogenesis, and cholesterogenesis (mevalonate pathway), resulting in steroid hormones, including estradiol.…”
Section: Origin Of Dha In the Brainmentioning
confidence: 96%